Enhancing Learning Outcomes and Student Responsibilities through Digital Fun Thinkers Media among Third Grade Elementary School Students - I Gusti Ayu Tri Agustiana; Ni Wayan Rati; I Wayan Ardana (Universitas Pendidikan Ganesha, 2026)
Low learning outcomes and responsibility in Grade III science subjects, particularly in the materials Various Types of Animals Around Us and Life Cycles of Living Things, are the main focus of this study. This research aims to develop and examine the effectiveness of Fun Thinkers Digital media as an interactive learning tool. The study employed the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation) involving 36 Grade III students. Data were collected through tests and questionnaires and analyzed descriptively and inferentially. The results indicate that the use of Fun Thinkers Digital media significantly improved learning outcomes, as shown by a t-test significance value of 0.040, and significantly enhanced responsibility with a significance value of 0.000. The media is considered feasible and effective due to its engaging, interactive presentation and its ability to encourage active student participation. Fun Thinkers Digital media can serve as an innovative alternative for elementary science learning.